Effects of lactic acid-producing bacteria as direct-fed microbials on the ruminal microbiome - Monteiro, H. F.; Lelis, A. L.J. [UNESP]; Fan, P.; Calvo Agustinho, B.; Lobo, R. R.; Arce-Cordero, J. A.; Dai, X.; Jeong, K. C.; Faciola, A. P. (American Dairy Science Association, 2022)
The objective of this study was to evaluate ruminal microbiome changes associated with feeding Lactobacillus plantarum GB-LP1 as direct-fed microbials (DFM) in high-producing dairy cow diets. A dual-flow continuous culture system was used in a replicated 4 × 4 Latin square design. A basal diet was formulated to meet the requirements of a cow producing 45 kg of milk per day (16% crude protein and 28% starch). There were 4 experimental treatments: the basal diet without any DFM (CTRL); a mixture of Lactobacillus acidophilus, 1 × 109 cfu/g, and Propionibacterium freudenreichii, 2 × 109 cfu/g [MLP = 0.01% of diet dry matter (DM)]; and 2 different levels of L. plantarum, 1.35 × 109 cfu/g (L1 = 0.05% and L2 = 0.10% of diet DM). Bacterial samples were collected from the fluid and particulate effluents before feeding and at 2, 4, 6, and 8 h after feeding; a composite of all time points was made for each fermentor within their respective fractionations. Bacterial community composition was analyzed through sequencing the V4 region of the 16S rRNA gene using the Illumina MiSeq platform. Sequenced data were analyzed on DADA2, and statistical analyses were performed in R (RStudio 3.0.1, https://www.r-project.org/) and SAS 9.4 (SAS Institute Inc.); orthogonal contrasts were used to compare treatments. Different than in other fermentation scenarios (e.g., silage or beef cattle high-grain diets), treatments did not affect pH or lactic acid concentration. Effects were mainly from overall DFM inclusion, and they were mostly observed in the fluid phase. The relative abundance of the phylum Firmicutes, family Lachnospiraceae, and 6 genera decreased with DFM inclusion, with emphasis on Butyrivibrio_2, Saccharofermentans, and Ruminococcus_1 that are fibrolytic and may display peptidase activity during fermentation. Lachnospiraceae_AC2044_group and Lachnospiraceae_XPB1014_group also decreased in the fluid phase, and their relative abundances were positively correlated with NH3-N daily outflow from the fermentors. Specific effects of MLP and L. plantarum were mostly in specific bacteria associated with proteolytic and fibrolytic functions in the rumen. These findings help to explain why, in the previous results from this study, DFM inclusion decreased NH3-N concentration without altering pH and lactic acid concentration.
Keywords: Butyrivibrio; Lactobacillus acidophilus; Lactobacillus plantarum; Propionibacterium freudenreichii